Transforming climate-smart agriculture through digital innovations: Kenya’s AgData Hub empowering millions of farmers - Chesoli, Rose (International Livestock Research Institute, 2025)
This brief presents findings from an internal review of Kenya’s AgData Hub, showing how AICCRA transformed the Kenya Agricultural Observatory Platform (KAOP) into a rich, inclusive digital ecosystem. The Hub delivers climate-smart advisories via web, SMS, USSD, radio, and more—reaching hundreds of thousands monthly and improving climate resilience, decision-making, and CSA adoption, while highlighting needs in coordination, data integration, and financing.